Clinical, cellular, and bioinformatic analyses reveal involvement of WRAP53 overexpression in carcinogenesis of lung adenocarcinoma - Xiao-Shuai Yuan; Long-Xiang Cao; Ye-Ji Hu; Fei-Chao Bao; Zhi-Tian Wang; Jin-Lin Cao; Ping Yuan; Wang Lv; Jian Hu (Tumor Biology)
Lung cancer, of which non-small cell lung cancer accounts for 80%, remains a leading cause of cancer-related mortality and morbidity worldwide. Our study revealed that the expression of WD repeat containing antisense to P53 (WRAP53) is higher in lung-adenocarcinoma specimens than in specimens from adjacent non-tumor tissues. The prevalence of WRAP53 overexpression was significantly higher in patients with tumor larger than 3.0 cm than in patients with tumor smaller than 3.0 cm. The depletion of WRAP53 inhibits the proliferation of lung-adenocarcinoma A549 and SPC-A-1 cells via G1/S cell-cycle arrest. Several proteins interacting with WRAP53 were identified through co-immunoprecipitation and liquid chromatography/mass spectrometry. These key proteins indicated previously undiscovered functions of WRAP53. These observations strongly suggested that WRAP53 should be considered a promising target in the prevention or treatment of lung adenocarcinoma.